Fragmentasi Jaringan dan Koalisi Advokasi dalam Tata Kelola Daerah Aliran Sungai: Pelajaran dari DAS Paguyaman, Indonesia (Network Fragmentation and Advocacy Coalitions in Watershed Governance: Lessons from the Paguyaman Basin, Indonesia) - Ivan Taslim; Sambas Basuni; Yanuar Jarwadi Purwanto; I Putu Santikayasa (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2025)
Watershed management in developing countries often faces persistent implementation gaps, despite the existence of sound environmental policies. This study investigates how stakeholder structure and coalition dynamics contribute to governance challenges in the Paguyaman Watershed, Gorontalo, Indonesia. Using a descriptive-exploratory approach, the MACTOR method was applied to analyze the relational structure among 15 key actors and 22 strategic objectives, based on a structured questionnaire, focus group discussions, and influence mapping. The results reveal a polarized stakeholder network divided into two coherent coalitions: a Government-Academic coalition oriented towards technocratic goals and a Civil Society coalition focused on socio-ecological justice. Divergence scores between the coalitions ranged from 0.81 to 0.87, indicating a high significant ideological conflict. Industry actors are found structurally isolated, with low convergence scores (<0.3), undermining collaborative efforts. The influence-dependence analysis identified four Driving Actors, seven Linking Actors, one Dependent Actor, and three Autonomous Actors. These imbalanced relational explain the failure of institutional coordination and the limited policy legitimacy. These findings emphasize that technical solutions alone are insufficient; effective watershed governance requires strategic interventions to bridge polarized coalition, engage isolated industry sectors, and strengthen coordinating actors to promote inclusive, and collaborative governance.